Mechanical Fruit Picker - Ameruddin, Haikal Daniel; Zafian, Ainul Ridhuan; Muhammad Imran Haziq Nazruddin; Basharie, Siti Mariam (Multidisciplinary Applied Research and Innovation, 2024)
The traditional method of picking fruit by hand and ladder is indeed tiring and usually takes a long time, especially if it involves a large quantity of harvested fruit. By using a fruit picking tool, the process of picking fruit can be easier, faster, and more effective. In this project, a simple mechanical fruit harvester was modified and manufactured. With its maximum length span of 3 meters, the fruit picker can reach high tree branches that were cultivated without much difficulty. Additionally, with its elastic and flexible chute, it has no problem holding too much fruit in it as the fruits will fall into the container placed below. Furthermore, the trigger handle connected to the lever principle has made the picker substantially easier to handle. Because it operates without a motor or electrical power, this tool is considered environmentally friendly. Based on results from performance studies, fruit picking can be done 40 to 50% faster compared to other tools. This tool is suitable for fruits like mangoes, rambutan, mangosteen and kedondong.